The many faces of poverty : Quantifying the deprivation costs of the 2001-2002 crisis in Argentina - Conconi, Adriana (2010)
This paper presents empirical evidence on the deprivation costs of the 2001- 2002 Argentinean crisis. The selected approach is multidimensional and focuses on four aspects of quality of life: labor, assets, education and income. These dimensions are constructed by multivariate data reduction techniques and then aggregated using the Bourguignon and Chakravarty's axiomatic multidimensional poverty measure. The main findings indicate that the crisis had larger costs on well-being dimensions which are tied to the economic cycle, such as income and labor. Costs were mild on structural aspects of wellbeing, such as assets and education. A sensitivity analysis shows that these results are robust to different deprivation lines.